Shaping Modern Liberalism Herbert Croly and Progressive Thought - Stettner, Edward A. (University Press of Kansas, 1993)
American ideals-liberty, equality, democracy, national unity-are bandied about by liberal politicians as a package deal, inseparably intertwined. But the words often flow together better as rhetoric than they mold together in theory. But, as Herbert Croly and his turnofthecentury contemporaries found, jelling these appealing yet often conflicting concepts into a liberal philosophy was not nearly as easy as embracing them in a campaign speech. In this first fulllength study of Herbert Croly's political theory, Edward Stettner analyzes Croly's writings and examines the events, experiences, and people who influenced Croly's thinking. In the process, he reveals Croly's significant influence on modern liberalism as classical liberal theory merged with progressive philosophy. Croly, founder of The New Republic, expounded on issues from the nationalization of railroads to the Espionage Act in his search for a middle way between socialism and capitalism. Stettner illustrates how Croly's political theory influenced the editorial position of one of the leading liberal journals and how his thought in turn was modified in reaction to national and world events, such as presidential elections and World War I. Stettner portrays Croly as a modest and conscientious intellectual who wholeheartedly came to embrace the progressive movement and consequently helped establish the framework for modern liberalism. In doing so, Stettner emphasizes how Croly's philosophy evolved and how Croly was drawn to the conclusion that a strong national government and individual rights could indeed coexist-if not always serenely-in a democratic society.